A multi-criteria group decision making framework for sustainability evaluation of sintering flue gas treatment technologies in the iron and steel industry. (20th February 2023) - Liu, Mengyue; Li, Yue; Xu, Yue; Chen, Leping; Wang, Qingsong; Ma, Qiao; Yuan, Xueliang
Abstract: The iron and steel industry (ISI) is at a critical stage of upgrading to ultra-low emission technologies in China. It is imperative to construct a life cycle sustainability evaluation framework as a guide for the selection of ultra-low emission technologies for the ISI. This research developed a novel multi-criteria group decision making framework. Four mature treatment technologies for sintering flue gas (SFG) were selected for analysis from an environmental, economic, and technological multi-dimensional perspective. The results of the life cycle assessment and life cycle costing are incorporated into the evaluation framework. The sustainability of ultra-low emission technologies was evaluated by combining Bayesian and hesitant fuzzy set theories for the first time. The results revealed that of the four alternatives considered, the most sustainable technology consists of semi-dry flue gas desulfurization, bag filter, and selective catalytic reduction denitrification. Triple sensitivity analysis and comparative analysis verified the consistency, robustness, and superiority of the proposed methodology. The interrelationship among criteria showed that technical maturity is key to enhancing the sustainability of ultra-low emission technologies, as it has a significant impact on costs and improves the environmental impact of the system. The conclusions provide optimization suggestions for further improving the sustainability of ultra-low emission technologies for SFG of ISI. Graphical abstract: Image 1 Highlights: Life cycle sustainability evaluation was combined with MCDM. A novel methodology for multi-criteria group decision making was constructed. The Bayesian BWM method was applied to determine the weights of the criteria. DEMATEL was used to model the intrinsic causality relationship of decision factors. Ultra-low emission technologies were ranked using hesitant fuzzy VIKOR method.